The Inventory List of the Library of the Vilnius Old Regula Carmelite Monastery at the St. George‘s Church: Publication of the Source - Kuliešienė, Erika (Bibliotheca Lituana, 2012)
This article presents the oldest source of information about the Vilnius Old Regula Carmelite Monastery library: the inventory list of the St. George’s Church library, compiled in 1677. Even though, in Polish historiography, considerable attention is accorded to the Vilnius St. George‘s Carmelite Monastery and its library, the 1677 inventory has not been included into any catalogue of inventories of the GDL’s church libraries. This inventory was for the first time introduced to the scientific community by A. Pacevičius. This article gives a short overview of the history of the Vilnius Carmelite Monastery at the St. George’s Church and of its library from its foundation to closure. The period of the compilation of the inventory is characterized as a crucial moment in the development of the library. At that time there were eight books in the church’s library, and 58 books, in the monastery’s library. Here we are publishing a facsimile of the inventory’s text and a transcript of the text in the language of the original. In the commentaries, with the greatest possible exactness, we are recreating the book list from rather scarce elements of book descriptions. This oldest source for the history of St. George Monastery library will doubtless be of interest not only for scholars in the history of the GDL, but also for both Lithuanian and foreign researchers of monastic book culture.
Keywords: none